(untitled) (Eurasian Journal of History, Geography and Economics, 2025)
This article analyzes the main directions of spiritual reforms implemented in Uzbekistan and finds practical confirmation that the path of spiritual reforms has been chosen as the right path for development today. Reforms based on ensuring the stability of sociopolitical and economic reforms in society as a result of spiritual and cultural renewal. are scientifically revealed.